New Nanomicellar Form of Latanoprost 0,005 % in Treatment Open Angle Glaucoma - A. S. Dukhanin; A. Sh. Zagidullina; G. A. Azamatova (Oftalʹmologiâ)
This article provides a review of Lanpressun®, a new formulations of latanoprost micellar nanoemulsion without benzaltonium chloride (BAK). The pharmacokinetics and pharmacodynamics of new formulations are presented. Due to innovative delivery system and absence of detergent preseravative (BAK, poliquaternium and others) Lanpressun® possess better tolerability and safety to ocular surface, that provides patients adherence to longer therapy. The article presents the results of clinical trials demonstrating high hypotensive efficacy of Lanpressun®. Literature analysis of studies on safety and effect on ocular surface shows good tolerability of preservativefree latanoprost nanoemulsion. The authors give the assessment of Lanpressun® future perspectives in treatment of patients with openangle glaucoma